Virtual multidisciplinary pain treatment: Experiences and feedback from children with chronic pain and their caregivers. - Ruskin, Danielle; Tremblay, Monique; Szczech, Klaudia; Rosenbloom, Brittany N; Mesaroli, Giulia; Sun, Naiyi; D'Alessandro, Lisa N (Physiotherapy Theory & Practice, 2024)
The onset of the coronavirus disease 2019 (COVID-19) necessitated a rapid transition to virtual care for chronic pain treatment. This study examined experiences of patients and caregivers who received virtual multidisciplinary pain treatment (MDT) for pediatric chronic pain between March 2020 and August 2021. A mixed methods design was implemented using qualitative interviews and quantitative satisfaction surveys. Satisfaction surveys were administered to a convenience sample of patients (aged 8 to 18; N = 20) and their caregivers (N = 20) who received MDT through an outpatient hospital pediatric chronic pain program. Interviews were conducted with a subset of these patients and their caregivers (n = 6). Analysis of interviews revealed four themes: 1) benefits of virtual care; 2) challenges of virtual care; 3) recommendations and evaluation of virtual care; and 4) patient preferences. Analysis of the satisfaction survey data revealed that while patients and caregivers were satisfied with many aspects of virtual care, 65% (n = 13) of patients reported a preference for in-person appointments, with caregivers showing equal preference for in-person and virtual appointments, though this was a non-significant difference (p =.37). Overall, both patients and caregivers stated a stronger preference for in-person physiotherapy sessions but were willing to have psychology sessions provided virtually. Finally, the most reported preference was for a hybrid model of care incorporating at least some in-person contact with providers. This study provides a rich exploration of virtual care for multidisciplinary pediatric chronic pain treatment. The current results may inform the future development of guidelines for virtual care delivery with pediatric chronic pain populations.